Synthesis and antimicrobial activity of some new 1-[4-(4-fluorobenzoylamino)-benzoyl]-4-substituted thiosemicarbazides - (:unkn) unknown (My University, 1995)
l-Aroyl-4-substituted thiosemicarbazides were obtained by the addition of 4-(4-fluorobenzoylamino)benzoylhydrazine to methyl, ethyl, propyl, allyl, cyclohexyl, phenyl and phenethyl isothiocyanates. The structures of the synthesized compounds were confirmed using UV, IR, 1H-NMR (for compounds 4c, 4g) and mass (for compounds 4b, 4c, 4g) spectral methods together with elemental analyses. None of the synthesized compounds has been reported previously. © Freund Publishing House, Ltd. 1995
Keywords: microbiology; spectral methods; substituted thiosemicarbazide; synthesis